Understanding the Effect of Iodide Ions on the Morphology of Gold Nanorods. (10th June 2018) - Amini, Mozhgan N.; Altantzis, Thomas; Lobato, Ivan; Grzelczak, Marek; Sánchez‐Iglesias, Ana; Van Aert, Sandra; Liz‐Marzán, Luis M.; Partoens, Bart; Bals, Sara; Neyts, Erik C.
Abstract: The presence of iodide ions during the growth of gold nanorods strongly affects the shape of the final products, which is proposed to be due to selective iodide adsorption on certain crystallographic facets. Therefore, a detailed structural and morphological characterization of the starting rods is crucial toward understanding this effect. Electron tomography is used to determine the crystallographic indices of the lateral facets of gold nanorods, as well as those present at the tips. Based on this information, density functional theory calculations are used to determine the surface and interface energies of the observed facets and provide insight into the relationship between the amount of iodide ions in the growth solution and the final morphology of anisotropic gold nanoparticles. Abstract : Depending on the amount of KI present during the overgrowth of gold nanorods, either rod‐ or dumbbell‐shaped particles can be obtained. Electron tomography and density functional theory calculations are employed to unravel the relationship between the amount of I ions in the growth solution and the final morphology of anisotropic gold nanoparticles.